American Vs Iranian University Websites: A Critical Discourse Analysis of About Pages - Mokhtarnia, Shabnam; Samar, Reza Ghafar- (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
In todays competitive world, official websites provide great venues for colleges and universities to express their institutional identity, an abstract representation of the complexity of the whole organization (Seidl 2005, p. 82) in order to leave an overriding impression on their potential clients and achieve institutional legitimacy and political power (DiMaggio & Powell, 1983).Thecombination of language and image areingredientsuniversity websites employ to promotetheir institutions and establish a distinct identity(e.g.,Anctil, 2008). Different sociocultural contexts, nonetheless, bear the potential to affect the way academic institutions represent their organizations on their official websites.This study, therefore,was an attempt to explore how top six Iranian and American universities used language to represent themselves on the About pages of their institutional websites. The resultsrevealed significant differences in the way these universities promoted themselves on their official partially related to larger socio-cultural forces functioning in their societies.